La cura del sapere con il pensiero. Il compito della filosofia morale - Moroncini, Bruno (Filosofia Morale/Moral Philosophy, 2022)
Inspired by Hegel, the essay first defines moral philosophy as the taking care of knowledge by thought. According to this definition, moral philosophy takes is concerned with the difficulties encountered by practical knowledge, i.e. the knowledge that guides the conduct of individuals and communities, when it is no longer adapted to new needs or new forms of life that have emerged from changes in society. Hence the need to separate ethics and morality: while the latter is conformist, the former is innovative, morality tends at all costs to reintroduce the new in the wake of tradition, ethics is inventive, it prepares new and unexpected ways of human living. This is followed by the analysis of two interpretative models of our historical actuality - Lacanian psychoanalysis and the Foucauldian concept of biopolitics - which also imply two hypotheses of formalisation of the pair ethics/morality. They appear as two important contributions to articulate the questions of where moral philosophy is going today and what its task might be.